Challenges and Recent Advances in Sustainable Oil and Gas Recovery and Transportation - Joshi Phd, Sanket; Joshi Phd, Sanket; Jadhawar, Prashant; Kumar, Asheesh (Gulf Professional Publishing, 2023)
Challenges and Recent Advances in Sustainable Oil and Gas Recovery and Transportation delivers a critical tool for today's petroleum and reservoir engineers to learn the latest research in EOR and solutions toward more SDG-supported practices. Packed with methods and case studies, the reference starts with the latest advances such as EOR with polymers and EOR with CCS. Advances in shale recovery and methane production are also covered before layering on sustainability methods on critical topics such as oilfield produced water. Supported by a diverse group of contributors, this book gives engineers a go-to source for the future of oil and gas. The oil and gas industry are utilizing enhanced oil recovery (EOR) methods frequently, but the industry is also tasked with making more sustainable decisions in their future operations. - Provides the latest advances in enhanced oil recovery (EOR), including EOR with polymers, EOR with carbon capture and sequestration (CCS), and hybrid EOR approaches - Teaches options in recovery and transport, such as shale recovery and methane production from gas hydrate reservoirs - Includes sustainability methods such as biological souring and oil field produced water solutions